2021
DOI: 10.1186/s12866-021-02231-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of S24–7 on the weight of progeny rats after exposure to ceftriaxone sodium during pregnancy

Abstract: Antibiotic exposure during pregnancy will adversely affect the growth of offspring; however, this remains controversial and the mechanism is poorly understood. To study this phenomenon, we added ceftriaxone sodium to the drinking water of pregnant rats and continuously monitored the body weight of their offspring. The results showed that compared with the control group, the offspring exposed to antibiotics during pregnancy had a higher body weight up to 3 weeks old but had a lower body weight at 6 weeks old. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…However, the beta-diversity analysis showed significant differences in the gut microbiota structure of the two groups. These results have been published before [ 21 , 24 ].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, the beta-diversity analysis showed significant differences in the gut microbiota structure of the two groups. These results have been published before [ 21 , 24 ].…”
Section: Discussionsupporting
confidence: 69%
“…A recent study of adverse drug reactions in pregnant women showed that the incidence of immune-related adverse events associated with ceftriaxone sodium was 18.4% [ 20 ], which may result in gut microbiota imbalance because of changes in the abundance of dominant taxa. Previously, we added ceftriaxone sodium to the drinking water of Sprague–Dawley rats during pregnancy and found the effect of ceftriaxone sodium on the weight of offspring, bacterial DNA sequencing also showed that structure of gut microbiota was markedly disrupted in the pregnant rats [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was possibly correlated with the antiobesity effect of TSs. In addition, as another gut metabolite correlated with body weight, glutaric acid was also involved in fatty acid degradation . In our study, a potentially beneficial effect of TSs was linked to the modulation of fatty acid metabolism by affecting gut microbiota.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, as another gut metabolite correlated with body weight, glutaric acid was also involved in fatty acid degradation. 65 In our study, a potentially beneficial effect of TSs was linked to the modulation of fatty acid metabolism by affecting gut microbiota. However, further studies are needed in the future to explore the potential role of other intestinal bacteria in host metabolism of fatty acids by TSs intervention in HFD-induced obesity.…”
Section: Discussionmentioning
confidence: 67%
“…At the family level, S24-7, Ruminococcaceae , and Lachnospiraceae were the most abundant in rabbits. S24-7 is negatively correlated with BW and had long-term adverse effects on growth ( 33 ), and plays important roles in amino acid metabolism and intestinal mucosal immunity ( 34 ). The decreased relative abundance of S24-7 implied the improved role of the addition of yucca extract and C. butyricum to rabbit feed.…”
Section: Discussionmentioning
confidence: 99%